Pemberdayaan Petani Berbasis Modal Sosial dan Kelembagaan - Dwi Wahyu Prasetyono (UII, 2017)
This study is intended to illustrate and explore the collective empowerment of farmer groups based on social capital. The collective context refers to the level of society, which involves three groups of farmer. This study also relates to the evaluation of the implementation process of village partner development program. During the process, empowerment is done by involving farmers' participation. Collective empowerment strengthens the roles and functions of farmer group organizations, in the accumulation of social forces that can bind and mobilize the participation of farmers in empowerment programs. The impact of changes that have occurred on partner farmer groups leads to a strengthening of their capabilities for social change and improved quality of life. Grow positive initiatives from them about what they need to do to strengthen their capabilities to realize the desired future.Â